Pengaruh Modernisasi Administrasi Perpajakan, Sanksi Pajak, Dan Pemahaman Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Muhammad Nabiel Azra; Rida Perwita Sari (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Tax revenue is the largest revenue and income received by the state to realize the welfare of the Indonesian people. This study aims to analyze the effect of modernization of tax administration, tax sanctions, and knowledge of taxation on compliance of individual taxpayers at KPP Pratama Surabaya Rungkut. The research was quantitative method and use primary data objects obtained from distributing questionnaires. The results of this study indicate that modernization of tax administration, tax sanctions, and knowledge of taxation affect the compliance of individual taxpayers at KPP Pratama Surabaya Rungkut. Keywords: Modernization Of Tax Administration, Tax Sanctions, Knowledge Of Taxation, Individual Taxpayer Sompliance